Biz venture: building future entrepreneurs / Nur’ Ain Achim … [et al.] - Achim, Nur’ Ain; Muhamad Yunus, Nor Sara Nadia; Ma'amor, Hairunnisa; Mohamad Basir, Faziatul Amillia; Abdul Rahman, Ramlee (Division of Research and Industry Linkages, 2017)
Biz Venture is real-life business simulation game for Faculty of Business and Management students. Students should apply their business theoretical knowledge and skills through this game. This game would be played out like explore race concept which encourages fast strategic thinking and decision-making. Thus, it is associated with the government aspiration for youth 'Transformasi Nasional’ (TN50) which grounded in one of its main circle; work and value creation. Aligned with the objective of the idea, this game helps in promoting sustainability, cultivating a high-income nation and a better technology-driven economy that provides more jobs and entrepreneurial opportunities for youth. Therefore, to ensure that, the introduction of Biz Venture in educational institutions like university plays a vital role as an important platform in preparing youth for demanding and challenging economy in the future. The module was initially developed to overcome the youth unemployment, especially among graduates. The lack of employability among local graduates has become a major concern to the Ministry of Education as statistics in 2015 shows 24% of the 273,373 graduates were unemployed. Due to that, this game has opened the door for innovative educational commercialization through the manual development of Biz Venture. This manual consists of everything you need to play the game with a very focus objectivity of educating young generations for an entrepreneurial mindset. This module is a new way of business simulation games through collaborative learning and expected to polish the critical thinking and application skills among the contestants. Currently, Biz Venture is being used as a competition for Kejohanan Piala Dekan held in Faculty of Business and Management and part of the Finishing School component. In the future, Biz Venture perhaps can bring new paradigm in bridging the gap between theories and the real-life application through fun, collaborative and interactive way of learning.